Analysis of Akad Salam (Pre-Order) in Online Buying and Selling Hanbali Mazhab Perspective (Case Study on Tokopedia Marketplace) - Habibah Moslem; Muhajirin; Hasbi Abdul Al-Wahhab KH; Nofrianto (Syarikat: Jurnal Rumpun Ekonomi Syariah, 2023)
The Hanbali Mazhab or Al-Hanabilah is a school of fiqh in Islam proposed and developed by Imam Ahmad bin Hanbal, a mujtahid and scholar of fiqh and hadith who came from Bahdad.  The development and potential of online buying and selling in Indonesia is very large, with a Muslim population of 207 million people or 87.2%. The most users of the marketplace are Muslim people who must comply with the rules of buying and selling in Islam, not only the halalness of the product but also transaction activities that must not conflict with Islamic sharia. In online buying and selling transactions in the marketplace, there are several types of contracts used, one of which is the salam contract in pre-order buying and selling. The purpose of this study is to analyze the use of salam (pre-order) contracts in online buying and selling transactions in the marketplace based on the Hanbali school of thought. This research uses a qualitative method, namely library research (literature study) with secondary data and primary data based on direct observation in the tokopedia marketplace. The results of this study indicate that the application of the salam (pre-order) contract in online buying and selling in the Tokopedia marketplace has fulfilled the pillars of the salam contract so that the transaction remains valid but in the application of the conditions there are still discrepancies.